Impact of helminth infection during pregnancy on cognitive and motor functions of one-year-old children. - Michael O Mireku; Michael J Boivin; Leslie L Davidson; Smaïla Ouédraogo; Ghislain K Koura; Maroufou J Alao; Achille Massougbodji; Michel Cot; Florence Bodeau-Livinec (Public Library of Science (PLoS), 2015)
OBJECTIVE:To determine the effect of helminth infection during pregnancy on the cognitive and motor functions of one-year-old children. METHODS:Six hundred and thirty five singletons born to pregnant women enrolled before 29 weeks of gestation in a trial comparing two intermittent preventive treatments for malaria were assessed for cognitive and motor functions using the Mullen Scales of Early Learning, in the TOVI study, at twelve months of age in the district of Allada in Benin. Stool samples of pregnant women were collected at recruitment, second antenatal care (ANC) visit (at least one month after recruitment) and just before delivery, and were tested for helminths using the Kato-Katz technique. All pregnant women were administered a total of 600 mg of mebendazole (100 mg two times daily for 3 days) to be taken after the first ANC visit. The intake was not directly observed. RESULTS:Prevalence of helminth infection was 11.5%, 7.5% and 3.0% at first ANC visit, second ANC visit and at delivery, respectively. Children of mothers who were infected with hookworms at the first ANC visit had 4.9 (95% CI: 1.3-8.6) lower mean gross motor scores compared to those whose mothers were not infected with hookworms at the first ANC visit, in the adjusted model. Helminth infection at least once during pregnancy was associated with infant cognitive and gross motor functions after adjusting for maternal education, gravidity, child sex, family possessions, and quality of the home stimulation. CONCLUSION:Helminth infection during pregnancy is associated with poor cognitive and gross motor outcomes in infants. Measures to prevent helminth infection during pregnancy should be reinforced.